2018
DOI: 10.1002/pmic.201800154
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Tissue Crosstalk via Shotgun Proteomic Analyses of Plasma Extracellular Vesicles

Abstract: Protein signaling between tissues, or tissue cross‐talk is becoming recognized as a fundamental biological process that is incompletely understood. Shotgun proteomic analyses of tissues and plasma to explore this concept are regularly challenged by high dynamic range of protein abundance, which limits the identification of lower abundance proteins. In this viewpoint article, it is highlighted how a focus on proteins contained within extracellular vesicles (EVs) not only partially addresses this issue, but can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…These EVs contain a vast array of signaling proteins and other molecules which can target specific organs, including the brain (see Figure 1 ). Therefore, EVs released during exercise may be one mechanism by which regular physical activity can slow or prevent the progression of neurodegenerative diseases such as AD [ 14 , 15 ], the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…These EVs contain a vast array of signaling proteins and other molecules which can target specific organs, including the brain (see Figure 1 ). Therefore, EVs released during exercise may be one mechanism by which regular physical activity can slow or prevent the progression of neurodegenerative diseases such as AD [ 14 , 15 ], the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…In separate studies, Ratajczak, Valadi, and Skog each showed that EVs contain RNA, and that EV-derived RNAs were transferable to recipient cells (Ratajczak et al, 2006;Valadi et al, 2007;Skog et al, 2008). Interestingly, Valadi et al found no clear correlation between EV expression and parent cell (Valadi et al, 2007) which is contradictory with later studies (Wei et al, 2017). The combination of the 2006 Nobel Prize being awarded to Fire and Mello for their discovery of RNA interference (Fire et al, 1998), and Valadi et al establishing the presence of small RNAs including micro-RNAs within EVs (Valadi et al, 2007;Skog et al, 2008) together pushed EV research into the spotlight.…”
Section: Historical Backgroundmentioning
confidence: 93%
“…The advantages of EV-focused MS analysis have been made clear through a number of studies including the identification of GPC1 as a marker of pancreatic cancer-derived EVs, genetic renal disease markers in urinary EVs, and novel myokines secreted during exercise in mammals (Gonzales et al, 2009 ; Melo et al, 2015 ; Whitham et al, 2018 ). Namely, EV separation and concentration prior to MS improves biomolecule discovery and identification by depleting highly abundant proteins and thereby sidestepping the dynamic range problem inherent within MS (Whitham and Febbraio, 2019 ). By separating EVs into density gradient fractions and then performing MS, for instance, one group was able to more sensitively uncover the heterogeneity among the protein content of EV subsets (Kowal et al, 2016 ).…”
Section: Experimental Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, current studies have highlighted that Filter-Assisted Sample Preparation (FASP) has improved performance of biological MS data [16, 118]. Moreover the high resolution MS analyzers, i.e., hybrid mass spectrometers, such as quadrupole time-of-flight (Q-Tof) and ion-trap like Orbitraps, show major advantages like excellent mass accuracy, high resolving power and fast duty cycles, thus they have become the most used for analyzing complex samples, as biological fluids, cells lysate or EVs [119].…”
Section: Mass Spectrometry (Ms)-based Analysis Of Extracellular Vementioning
confidence: 99%